Analysis of genetic and clinical factors associated with buprenorphine response. (1st October 2021) - Crist, Richard C.; Vickers-Smith, Rachel; Kember, Rachel L.; Rentsch, Christopher T.; Xu, Heng; Edelman, E. Jennifer; Hartwell, Emily E.; Kampman, Kyle M.; Kranzler, Henry R.
Highlights: We report the first GWAS of buprenorphine treatment response. We identified six loci as nominally associated with treatment response. A hepatitis C diagnosis was associated with reduced odds of treatment response. Abstract: Background: Buprenorphine, approved for treating opioid use disorder (OUD), is not equally efficacious for all patients. Candidate gene studies have shown limited success in identifying genetic moderators of buprenorphine treatment response. Methods: We studied 1616 European-ancestry individuals enrolled in the Million Veteran Program, of whom 1609 had an ICD-9/10 code consistent with OUD, a 180-day buprenorphine treatment exposure, and genome-wide genotype data. We conducted a genome-wide association study (GWAS) of buprenorphine treatment response [defined as having no opioid-positive urine drug screens (UDS) following the first prescription]. We also examined correlates of buprenorphine treatment response in multivariable analyses. Results: Although no variants reached genome-wide significance, 6 loci were nominally significant (p < 1 × 10 −5 ), four of which were located near previously characterized genes: rs756770 ( ADAMTSL2 ), rs11782370 ( SLC25A37 ), rs7205113 ( CRISPLD2 ), and rs13169373 ( LINC01947) . A higher maximum daily buprenorphine dosage (aOR = 0.98; 95 %CI: 0.97, 0.995), greater number of UDS (aOR = 0.97; 95 %CI: 0.96, 0.99), and history of hepatitis C (HCV) infection (aOR = 0.71; 95 %CI: 0.57, 0.88) were associated with a reduced odds of buprenorphine response. Older age (aOR: 1.01; 95 %CI: 1.000, 1.02) was associated with increased odds of buprenorphine response. Conclusions: This study had limited statistical power to detect genetic variants associated with a complex human phenotype like buprenorphine treatment response. Meta-analysis of multiple data sets is needed to ensure adequate statistical power for a GWAS of buprenorphine treatment response. The most robust phenotypic predictor of buprenorphine treatment response was intravenous drug use, a proxy for which was HCV infection.